165k views
5 votes
Solve quadratic formulax^2-4x+3=0

User Zygimantas
by
5.7k points

1 Answer

2 votes

The general formula for a equation of the form:


ax^2+bx+c=0

is:


x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}

In this case we notice that a=1, b=-4 and c=3. Plugging this values in the general formula we get:


\begin{gathered} x=\frac{-(-4)\pm\sqrt[]{(-4)^2-4(1)(3)}}{2(1)} \\ =\frac{4\pm\sqrt[]{16-12}}{2} \\ =\frac{4\pm\sqrt[]{4}}{2} \\ =(4\pm2)/(2) \end{gathered}

then:


x_1=(4+2)/(2)=(6)/(2)=3

and


x_2=(4-2)/(2)=(2)/(2)=1

Therefore, x=3 or x=1.

User Sam McAfee
by
5.9k points